Experiment, theory, and the keratocyte: An ode to a simple model for cell motility. (April 2020) - Mogilner, Alex; Barnhart, Erin L.; Keren, Kinneret
Abstract: Lamellipodial locomotion of fish keratocytes is one of the simplest examples of actin-based motility. In the last four decades, fruitful collaborations between experimentalists and theorists have resulted in a detailed mechanistic understanding of the self-organized lamellipodial engine powering keratocyte motility. Here we review the mechanical mechanisms underlying keratocyte migration, highlighting the interplay between modeling and experiments that led to insights regarding the dynamics of actin network organization, cell shape, and self-polarization. We discuss how to apply lessons learnt from keratocytes to understand cell migration in more complex, physiological contexts.